Aid effectiveness on economic growth in disaggregation by type of aid - RYU, Kyungnam (KDI School, 2015)
The purpose of this study is to investigate the effectiveness of foreign aid on economic growth of developing countries by type of aid with OECD DAC (Development Assistance Committee) data. As methodology, it applies econometric approaches to analyze panel data of cross-country samples spanning for twelve years. One important contribution of this study to the continuing aid-growth discussion is to disaggregate aid into sub-categories and demonstrate more specific empirical findings on the effectiveness of each aid type on a macro performance indicator of some of the DAC recipient countries. Among various aid types, particular attention is paid to Programme aid, Project aid, and Technical assistance. Aid and other country specific data are collected from the OECD CRS (Creditor Reporting System) and World Bank DataBank to test the hypothesis that Programme aid is the most effective on economic growth in developing economies than the other two types of aid are. The statistical analysis by using more than 60 countries from 2002 to 2013 shows positive effects of General budget support belonging to Programme aid and negative effects of Project aid, but neither of them is statistically significant. Technical assistance by experts has positive and statistically significant effects on per capita GDP growth while Technical assistance for fellowship has negative and statistically significant effects on economic development. It can be interpreted that one percent increase in technical assistance for experts leads to about one percent increase in per capita GDP growth in aid recipient countries on average. Although the econometric tests indicate the superiority of the Random Effects estimation method with the data, each effect of the Programme aid, Project aid, and Technical assistance on the economic growth was not different among estimation methods, boosting the robustness of my estimation results.
Thesis(Master) --KDI School:Master of Development Policy,2015